Oligorecurrence Non–small Cell Lung Cancer After Failure of First-Line Chemotherapy: Computed Tomography–Guided 125I Seed Implantation vs. Second-Line Chemotherapy - Wang, Hao; Lu, Jian; Zheng, Xiao-Ting; Zha, Jun-Hao; Jing, Wen-Dong; Wang, Yong; Zhu, Guang-Yu; Zeng, Chu-Hui; Chen, Lei; Guo, Jin-He (Frontiers in Oncology, 2020)
Purpose: To compare the efficacy and safety of CT-guided 125I seed implantation with second-line chemotherapy in treatment of oligorecurrence NSCLC after failure of first-line chemotherapy. Materials and Methods: Data of oligorecurrence NSCLC patients after failure of first-line chemotherapy at two institutions were retrospectively reviewed from January 2013 to July 2018. A total of 53 patients who received the treatment of 125I seed implantation and second-line chemotherapy were eligible for this study. In Group A, 25 patients received CT-guided permanent 125I seed implantation, while in Group B, 28 patients received second-line chemotherapy. The outcomes were measured in terms of disease control rate, overall survival, quality of life, and complications. Results: The median follow-up period was 13 months (range 5 – 42 months). Disease control rate in Group A was higher than that in Group B (70.8% vs 42.3%, p = 0.042) at 6th months after treatment. The median overall survival was 12.8 months (95% confidence interval: 10.5–15.1) in Group A and 15.2 months (95% confidence interval: 12.2–18.2) in Group B, with no significant difference (p = 0.847). Since the 4th month, the number of patients in Group A with a non-decreasing Karnofsky Performance Score was more than that in Group B (p < 0.05). The incidence of grade 3 or higher complications in Group A was lower than that in Group B (p < 0.05). Conclusion: Radioactive 125I seed implantation is safe and feasible in selected NSCLC patients with oligorecurrence after failure of first-line chemotherapy and seems to provide a better long-term QOL in these patients compared with second-line chemotherapy.